2017
DOI: 10.5815/ijem.2017.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Relating Interactive System Design and Information Theory from Information Leakage Perspective

Abstract: In contemporary interactive software system design, to maintain equilibrium between usability and security is a challenging task because strictly enforced security policies directly affect the usability of the software. As a solution to this problem, information theoretic measure of information leakage in interactive system design has been proposed in the present work. The present paper first models the software system as a coloured Petri net model and after that using information theory and Petri net algebra;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Wiener (1954) suggested that for organizational information processing systems, to understand threshold and energy at a fine-grained level, information theory and Shannon’s entropy concept can be used. For interactive systems, Anjaria and Mishra (2017b) have discussed that how threshold can be understood using information theory.…”
Section: Use Of Generalized Cybernetics-based Situation Awareness Model In Implementing Situation-aware Information Security Risk Managemmentioning
confidence: 99%
“…Wiener (1954) suggested that for organizational information processing systems, to understand threshold and energy at a fine-grained level, information theory and Shannon’s entropy concept can be used. For interactive systems, Anjaria and Mishra (2017b) have discussed that how threshold can be understood using information theory.…”
Section: Use Of Generalized Cybernetics-based Situation Awareness Model In Implementing Situation-aware Information Security Risk Managemmentioning
confidence: 99%